Essays on asset pricing - Gafka, B (2022)
This dissertation presents the reader with three empirical analyses in the asset pricing realm. The first chapter, Mind the (Trade) Gap! Stock market implications of barriers to trade, looks into the impact of free trade agreements on stock prices. It quantifies the effect of the United Kingdom’s departure from the European Union (the so-called Brexit) on European equity prices. In this chapter, I identify an overwhelmingly negative response of the cross-section of European equities to this decision and show that varying degrees of Brexit exposure explain differences in returns on European stocks over the Brexit negotiations period (between July 2016 and December 2019). Both results are more pronounced in the UK than in the EU. I go on to exploit this cross-sectional variation in equity returns to construct a Brexit mimicking portfolio tracking latent Brexit shocks over time. This portfolio explains a significant amount of time-series variation of European stock market in the post-referendum period. Finally, its correlations with the European stock market indices suggest Brexit constituted far greater and more lasting a shock to the local United Kingdom’s than the European Union’s economy. The second chapter, Sources of Return Predictability, develops an approach to determine whether known return predictors are proxies for fundamental risk in the economy or not. To this end, it builds on previous literature which has documented differences between days when important macroeconomic news is scheduled to be released onto the market and the remaining days. The chapter shows that known stock return predictors forecast returns accrued on either announcement or non-announcement days but never on both types of days. Interestingly, most known predictors forecast non-announcement day returns only. The paper further shows that the excess volatility puzzle of Shiller 1981 is predominantly a non-announcement days puzzle. Taken together, these results suggest that known return predictors forecast the excess volatility component of the stock market. This is joint work with Pavel Savor and Mungo Wilson. The third chapter, Old wine in new bottles. Are industry risks still not understood?, examines the relationship between Fama-French risk factors and industry-specific returns. It shows that industry indices can consistently explain large shares of risk premiums documented by Fama and French. Similarly, Fama-French univariate and multivariate sort portfolios commonly used in the literature show strikingly consistent trends with respect to co-movement with a limited set of industries. Moreover, as expected in a commercially integrated world, geographic zone factors also constitute portfolios of industry indices. Together, these results suggest that various risk premiums credited to existence of the corresponding risk factors can in fact just be combinations of industry-specific risks which nature has just been insufficiently understood up till now. Taken together, these three chapters contribute to the growing body of literature on markets’ informational efficiency and the impact of information arrival on investors’ beliefs.